2017
DOI: 10.22354/in.v0i0.704
|View full text |Cite
|
Sign up to set email alerts
|

Practical Recommendations for Preoperative Skin Antisepsis

Abstract: The search for strategies for the reduction of Surgical Site infection (SSI) is a priority, given the impact those infections have on the outcome of the patients. The preope rative patient skin antisepsis, has recently gained greater significance in the prevention of SSI, as one of the critical factors, which can be intervened and can reduce the risk of infection. In recent years, comprehensive investigations have been published, not only dedicated to the comparison of antiseptic solutions, application techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
6
0
4
Order By: Relevance
“…CAE gelişimine neden olan en önemli faktörlerden bir tanesini hastanın kendi florası olduğu bilinmektedir (10,11). Bu nedenle CAE'nin önlenmesinde deri hazırlığı önem taşımaktadır (12).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…CAE gelişimine neden olan en önemli faktörlerden bir tanesini hastanın kendi florası olduğu bilinmektedir (10,11). Bu nedenle CAE'nin önlenmesinde deri hazırlığı önem taşımaktadır (12).…”
Section: Discussionunclassified
“…Ayrıca, ameliyattan önce hastanın banyo yapması hastanın kendisini rahat ve huzurlu hissetmesine de yardımcı olmaktadır (13). Bunun için hastaların ameliyattan önceki gece ya da ameliyat sabahı sabun (antimikrobiyal/antimikrobiyal olmayan) ya da antiseptik ürün ile duş alması/banyo yapması önerilmektedir (1,11,14). Bu çalışmada hemşirelerin az bir kısmı çalıştıkları kurumda hastalara ameliyat öncesi rutin olarak duş/banyo yaptırıldığını belirtmişlerdir.…”
Section: Ameliyat öNcesi Duş/banyounclassified
“…According to the food and drugs administration (FDA) these antiseptic solutions can reduce the number of transient and permanent microorganisms in the surgical field rapidly (10 minutes after the painting) and suppresses its growth until 6 hours. 37 Frantizides et al reported that SSI mostly causes by the skin commensals predominately gram-positive cocci. They compared two groups; one received ABP, and the other group had skin preparation with CH.…”
Section: On the Other Hand Those Who Are In Support Of Abp Argue Thatmentioning
confidence: 99%
“…The use of adhesive dressings over the incision site may decrease the risk of contamination with residual flora of the skin. 37 Samsal et al communicated with the ten commandments for preventing PSI: (1) Whenever possible use disposable trocars and instruments, and adequate stock of properly sterilized reusable trocars as stand-by or to cover all the surgical procedures for the day where disposable trocar and instruments are not available, (2) Use of Laparoscopic hand instruments which are autoclave compatible, (3) Instruments with limited joints, and provision to clean the debris collected in its crevices should be used, (4) Proper cleaning of the instrument after dismantling, (5) The concentration and the contact time with a liquid sterilizing agent, and cycles of use for sterilizing instruments should be followed properly according to the protocol,(6) In case of long OT line-up, instrument sterilization to be done with either plasma sterilizer or ethylene oxide,(7) Separate instrument sets for all the different subject specialties and avoiding sharing of instruments, (8) Surgical steps should be executed meticulously so as to avoid bile spillage in the operative area/port site, (9) Use of non-porous specimen retrieval bags, and (10) Meticulous cleaning of the port site before closure. 13 The PSIs will present as a seropurulent discharge from the port sites along with inflammatory changes in and around the port site.…”
Section: On the Other Hand Those Who Are In Support Of Abp Argue Thatmentioning
confidence: 99%
“…Skin preparation with proper antiseptics according to Álvarez et al 2018. 14 3. Sterile dressings and proper wound care to protect the incision according to Bradford and Hamerslagh, 2018.…”
Section: Standardized Antimicrobial Prophylaxis Policy According To Imentioning
confidence: 99%